Peningkatan Motivasi Belajar Siswa Kelas VII SMP Negeri 2 Lubuk Sikaping Menggunakan Media Video Pembelajaran - Adrin, Elit (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to enhance students' learning motivation through the use of instructional video media. The research was conducted in two cycles, involving 25 seventh-grade students at SMP Negeri 2 Lubuk Sikaping. The results indicate that the use of engaging and interactive instructional videos significantly increased students' learning motivation. In Cycle I, the average motivation score of students improved from 59.20 to 74.08. In Cycle II, after utilizing more interactive videos, students' motivation increased even more, with the average score rising from 74.48 to 85.84. This improvement shows that instructional video media can stimulate students' interest to be more active in the learning process and better understand the taught material.